Phenol degradation by Acinetobacter sp. in the presence of heavy metals - Ahmad S.A.; Shamaan N.A.; Syed M.A.; Dahalan F.A.; Abdul Khalil K.; Ab Rahman N.A.; Shukor M.Y. (National Science Foundation, 2024)
The purpose of this study was to investigate the ability of Acinetobacter sp. strain AQ5NOL 1 immobilised in gellan gum beads to degrade phenol in the presence of heavy metals. Seven different heavy metals, namely, As5+, Cu2+, Cd2+, Ni2+, Cr6+, Pb2+, and Hg2+ at 1 ppm were tested. Results of the study showed that degradation of phenol by free cells was inhibited by Hg2+, Cu2+ and Cr6+ after 48 hours of incubation by 97.91 %, 77.58 % and 75.26 %, respectively. Only Hg2+ and Cr6+ inhibited phenol degradation by immobilised Acinetobacter cells in 18 hours by 67.55 % and 53.19 %. Phenol degradation by immobilised cells was affected when Cr6+ and Hg2+ concentrations exceeded 0.5 and 0.1 ppm, respectively. However, inhibitory effects of heavy metals can be overcome by prolonging the incubation time for immobilised Acinetobacter sp. strain AQ5NOL 1 from 18 hours to 24 and 30 hours for Cr6+ (46.80%) and Hg2+ (21.40%), respectively. 2017, National Science Foundation. All rights reserved.